Association of prognostic nutritional index with risk of contrast induced nephropathy: A meta-analysis - Chang, Wei-Ting; Sun, Cheuk-Kwan; Wu, Jheng-Yan; Huang, Po-Yu; Liu, Ting-Hui; Chang, Ying-Jen; Lin, Yao-Tsung; Kang, Fu-Chi; Hung, Kuo-Chuan (Frontiers in Nutrition, 2023)
Background: Although prognostic nutritional index (PNI) has been frequently applied in patients with malignancy or those during postoperative recovery, whether it is also an optimal indicator of the risk of contrast-induced nephropathy (CIN) in patients receiving coronary angiography remains uncertain. This meta-analysis aimed at investigating the clinical association of PNI with the risk of CIN in patients receiving coronary angiography or percutaneous coronary intervention. Methods: Embase, Medline, Cochrane Library, and Google scholar were searched for studies until January 2023. The relationship between CIN risk and PNI (i.e., low vs. high) (primary outcome) as well as other variables (secondary outcomes) were analyzed using a random-effects model. Results: Overall, 10 observational studies with 17,590 patients (pooled incidence of CIN: 18%) were eligible for analysis. There was a higher risk of CIN in patients with a low PNI compared to those with a high PNI [odd ratio (OR)=3.362, 95% confidence interval (CI): 2.054 to 5.505, p<0.0001, I2=89.6%, seven studies, 12972 patients, certainty of evidence: very low]. Consistently, a lower PNI was noted in patients with CIN compared to those without (Mean difference=-5.1, 95% CI: -6.87 to -3.33, p<0.00001, I2=96%, eight studies, 15516 patients, certainty of evidence: very low). Other risks of CIN included diabetes and hypertension, while male gender and the use of statins were associated with a lower risk of CIN. Patients with CIN were older, had a higher creatinine level, and received a higher contrast volume compared to those without. On the other hand, pre-procedural albumin, estimated glomerular filtration rate, ejection fraction, hemoglobin, lymphocyte ratio were found to be lower in patients with CIN than in those without. Conclusion: This meta-analysis highlighted an inverse association of PNI with the risk of CIN, which required further studies for verification.